Avaliação da capacidade antirradicalar do neurosporeno: um estudo teórico - Monego, Débora Luana (2016)
Carotenoids are natural pigments known for being vitamin A precursors and for their important biological activities, such as antioxidant activity. In this study, the free radical scavenger capacity of neurosporene was evaluated and compared to the one of lycopene, which is the most efficient radical scavenger amongst carotenoids. The Density Functional Theory (DFT), combined with the B3LYP functional and 6-31G(d) basis set, were employed to optimize the geometries of the studied molecules in gas phase and to calculate their correspondent single-point energies. Thus, the ionization energy and the electron affinity were calculated in order to assess the antiradical capacity according to the electron transfer mechanism. From these values, neurosporene and lycopene’s radical potentials were compared. Neurosporene presented lower antioxidant activity than lycopene, what was already expected due to the number of conjugated double bonds. Notwithstanding, neurosporene may still be considered a good free radical scavenger. The electron-transfer between neurosporene and the superoxide radical anion is more likely to occur with electrons being transferred from the free radical to the carotenoid, due to the negative charge of this radical. This interaction must be further evaluated and thermodynamic energies must be assessed to understand how it occurs in vivo.